2007
DOI: 10.1590/s1415-54192007000400013
|View full text |Cite
|
Sign up to set email alerts
|

Telerradiografias obtidas em posição natural da cabeça alteram as grandezas cefalométricas?

Abstract: Objetivo: o objetivo deste estudo foi comparar a real variação entre as medidas cefalométricas realizadas em telerradiografias laterais de um mesmo indivíduo, obtidas em posição natural da cabeça (PNC) e na técnica padrão, onde o plano de Frankfurt foi posicionado paralelamente ao solo. Foi realizada a análise facial, comparando as medidas de postura, perfil facial e medidas ântero-posteriores. Metodologia: a amostra foi composta por 50 telerradiografias laterais de indivíduos brasileiros, sendo 25 do gênero f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
2
0
3
Order By: Relevance
“…It is considered feasible such investigations, given that research in the area of orthodontics have shown that the natural head posture is reproducible in different radiographs , and allows a safer and closer planning to the reality of patients 19 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is considered feasible such investigations, given that research in the area of orthodontics have shown that the natural head posture is reproducible in different radiographs , and allows a safer and closer planning to the reality of patients 19 …”
Section: Resultsmentioning
confidence: 99%
“…There is scientific evidence that may have differences in facial analysis depending on the positioning of the head during the exam, because often the natural posture of the head does not coincide with the Frankfurt plane in horizontal 19 . In a study15 conducted with children the authors found a correlation between the results of the assessment of facial performed by analyzing Ricketts and Ávila method 12 , and claim that they can be used independently.…”
Section: Discussionmentioning
confidence: 99%
“…As diferentes posições da cabeça na realização das avaliações também interferem, visto que as medidas angulares utilizadas para o cálculo do Índice Vert e a análise facial são alteradas de acordo com o posicionamento 20 .…”
Section: Discussionunclassified
“…Os exames de TCFC foram realizados em face total na mesma clínica radiológica, utilizando mesmo equipamento e mesmas configurações, com os parâmetros de aquisição em 120 kVp, 37,1 mA, 17,8 segundos, tamanho de volume renderizado em 17 x 23 cm (FOV) e resolução de 0,3 mm 3 de voxel, através do aparelho iCAT ® (Imaging Sciences International LLC, Hatfield, PA, USA). A orientação da posição da cabeça dos pacientes na obtenção do exame, como forma padrão, era posição natural da cabeça (PNC) 7,8,11,12 .…”
Section: Materiais E Métodounclassified